Teaching & Learning Guide for: Whose War Was It Anyway? Some Australian Historians and the Great War - Bongiorno, Frank (History compass, 2009)
The article is an attempt to assess a body of historical and polemical writing on Australia's entry into the First World War. It also offers, from page 70 through to page 74, an alternative to the kind of understanding of Australian participation in the war with which we take issue elsewhere in the article. The piece was inspired by our engagement with the important writing of John Moses, who was for some years a valued colleague at the University of New England; in Frank's case, as a university lecturer teaching a course on War and Society in Twentieth-century Australia and a scholar with a long-standing interest in Australian historiography, and in Grant's, as a doctoral candidate being supervised by Frank and researching a thesis on Australian responses to the outbreak of the war. Grant, who was in the process of completing his thesis when we published this article, has since finished and is revising his work for publication. He also produced an earlier historiographical piece arising from his doctoral work : ‘"Unbounded Enthusiasm": Australian Historians and the Outbreak of the Great War’, Australian Journal of Politics and History, 3/3 (September 2007): 360-74. Like any piece of academic historical writing, our article represented an attempt to solve a ‘problem’. The ‘problem’, as we saw it, was why a group of historians and political commentators had spent so many words contesting a view which they presented as mistaken historical orthodoxy, but which we were unable to find articulated in the major writings on Australia and the Great War with which we were familiar. The writers with whom we argued suggest that, contrary to the claims of radical-nationalist historians, the Great War was truly Australia's war, and one in which Australia's vital interests were at stake. Our purpose in writing our article was not to contest their particular claims about the national interest, but rather to interrogate aspects of their own methodology and assumptions, and to suggest an alternative. In particular, we argued that their work came out of a focus on ‘high politics’ and diplomacy, and that a closer look at the contemporary discourse suggests greater complexity and ambiguity about the significance of the war for Australians. We suggested that it was wrong to impose a single meaning on Australian participation in the war derived from an understanding of diplomatic history, and that attempts to do so needed to be understood in the context of modern Australian conservative intellectuals’ affirmative attitude towards the nation's imperial inheritance.